2019
DOI: 10.1002/esp.4594
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing beach intertidal bar systems using multi‐annual LiDAR data

Abstract: Intertidal bars are common in mesotidal/macrotidal low‐to‐moderate energy coastal environments and an understanding of their morphodynamics is important from the perspective of both coastal scientists and managers. However, previous studies have typically been limited by considering bar systems two‐dimensionally, or with very limited alongshore resolution. This article presents the first multi‐annual study of intertidal alongshore bars and troughs in a macrotidal environment using airborne LiDAR (light detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…In addition to this system of bars, the larger sedimentary feature indicated accretes, expanding northwards by around 200 m. This confirms local anecdotal knowledge, scientific observations and modelled predictions about this system with the dominant longshore current driving sediment northwards and migration of sediment onshore under typical conditions. See Miles et al (2019) for a description of these intertidal bar systems along the Fylde coast that closely aligns with the radar-derived characteristics. Further analysis aims to show the effect of storms and changes in wave direction on sediment migration at this site.…”
Section: Monitoring Geomorphological Changementioning
confidence: 61%
“…In addition to this system of bars, the larger sedimentary feature indicated accretes, expanding northwards by around 200 m. This confirms local anecdotal knowledge, scientific observations and modelled predictions about this system with the dominant longshore current driving sediment northwards and migration of sediment onshore under typical conditions. See Miles et al (2019) for a description of these intertidal bar systems along the Fylde coast that closely aligns with the radar-derived characteristics. Further analysis aims to show the effect of storms and changes in wave direction on sediment migration at this site.…”
Section: Monitoring Geomorphological Changementioning
confidence: 61%
“…In contrast, the method employed to build the model described in this article can be applied to any morphological data set with sufficient measurements or any study site where such measurements can be carried out. Additionally, the model's poor prediction of long-term large volume change challenges the significance of studies using low measurement frequency (e.g., a survey per year) [46].…”
Section: Advantages Of This Innovative Modelmentioning
confidence: 99%
“…Morphodynamics of beaches with multiple intertidal bar-trough systems have been well documented over the past (e.g., [35,46,47,54,55]). They mainly occur on restricted coasts with a surplus of sand, exposed fetch-limited waves, and large tidal range above 3 m [56].…”
Section: Findings In Bar Morphodynamicsmentioning
confidence: 99%
“…Miles et al . () also working on longer‐term morphodynamics examined nearshore bar movements in three dimensions using light detection and ranging (LiDAR) within a macrotidal environment in the UK. Over a 17‐year period the (3–4) bar positions were characterized for a 17 km stretch and showed distinct alignment with the predominant wave approach direction.…”
mentioning
confidence: 99%
“…However, their findings showed that establishing the relation between forcing and response is not a straightforward task due to the complexities of that control of coastal morphodynamics. Miles et al (2019) also working on longer-term morphodynamics examined nearshore bar movements in three dimensions using light detection and ranging (Li-DAR) within a macrotidal environment in the UK. Over a 17year period the (3-4) bar positions were characterized for a 17 km stretch and showed distinct alignment with the predominant wave approach direction.…”
mentioning
confidence: 99%